Correlations Between Vertebral and Femoral Neck T-Scores in Turkish Female Population - Nurettin Aka; Murat Api; Gültekin Köse; Pınar Kumru (Medical Network, 2007)
OBJECTIVE: The aim of this study was to evaluate the correlation of dual-energy X-ray absorbtiometry measurements between the spine and femoral neck to predict bone mineral density (BMD) as defined according to the WHO classification in Turkish population. STUDY DESIGN: Five hundred and ninety-two postmenopausal women aged 39-74 years were investigated. There was significant and strong correlation between BMD measurements, with r:0,69-0,74 p<0,05. RESULTS: The cut off values of the femoral neck and ward triangle BMD that allow the identification with 95% sensivity of postmenopausal women with either lumbal spines T-score< -1, correspond to a T score -0,4 (femoral neck) and +0,05 ( ward triangle). CONCLUSION: However, this study highlights the difficulties in using a unique T-score that could be applied to different sites to diagnose osteoporosis.